Optimal. Leaf size=22 \[ 2 x^2 \left (3+\frac {2 \left (-2-\frac {1}{e}\right ) x}{1+x}\right ) \]
________________________________________________________________________________________
Rubi [A] time = 0.05, antiderivative size = 38, normalized size of antiderivative = 1.73, number of steps used = 4, number of rules used = 3, integrand size = 36, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.083, Rules used = {12, 27, 1850} \begin {gather*} -\frac {2 (2+e) x^2}{e}+\frac {4 (1+2 e) x}{e}+\frac {4 (1+2 e)}{e (x+1)} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 12
Rule 27
Rule 1850
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\frac {\int \frac {-12 x^2-8 x^3+e \left (12 x-4 x^3\right )}{1+2 x+x^2} \, dx}{e}\\ &=\frac {\int \frac {-12 x^2-8 x^3+e \left (12 x-4 x^3\right )}{(1+x)^2} \, dx}{e}\\ &=\frac {\int \left (4 (1+2 e)-4 (2+e) x-\frac {4 (1+2 e)}{(1+x)^2}\right ) \, dx}{e}\\ &=\frac {4 (1+2 e) x}{e}-\frac {2 (2+e) x^2}{e}+\frac {4 (1+2 e)}{e (1+x)}\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.02, size = 37, normalized size = 1.68 \begin {gather*} -\frac {4 \left (\frac {-1-2 e}{1+x}-3 (1+e) (1+x)+\frac {1}{2} (2+e) (1+x)^2\right )}{e} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.75, size = 35, normalized size = 1.59 \begin {gather*} -\frac {2 \, {\left (2 \, x^{3} + {\left (x^{3} - 3 \, x^{2} - 4 \, x - 4\right )} e - 2 \, x - 2\right )} e^{\left (-1\right )}}{x + 1} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.29, size = 37, normalized size = 1.68 \begin {gather*} -2 \, {\left (x^{2} e + 2 \, x^{2} - 4 \, x e - 2 \, x - \frac {2 \, {\left (2 \, e + 1\right )}}{x + 1}\right )} e^{\left (-1\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.17, size = 26, normalized size = 1.18
method | result | size |
norman | \(\frac {6 x^{2}-2 \left ({\mathrm e}+2\right ) {\mathrm e}^{-1} x^{3}}{x +1}\) | \(26\) |
gosper | \(-\frac {2 x^{2} \left (x \,{\mathrm e}-3 \,{\mathrm e}+2 x \right ) {\mathrm e}^{-1}}{x +1}\) | \(27\) |
default | \({\mathrm e}^{-1} \left (-2 x^{2} {\mathrm e}+8 x \,{\mathrm e}-4 x^{2}+4 x -\frac {4 \left (-2 \,{\mathrm e}-1\right )}{x +1}\right )\) | \(40\) |
risch | \(-2 x^{2}+8 x -4 x^{2} {\mathrm e}^{-1}+4 \,{\mathrm e}^{-1} x +\frac {4 \,{\mathrm e}^{-1}}{x +1}+\frac {8 \,{\mathrm e}^{-1} {\mathrm e}}{x +1}\) | \(42\) |
meijerg | \(-12 \,{\mathrm e}^{-1} \left (\frac {x \left (6+3 x \right )}{3 x +3}-2 \ln \left (x +1\right )\right )+\left (-4 \,{\mathrm e}-8\right ) {\mathrm e}^{-1} \left (-\frac {x \left (-2 x^{2}+6 x +12\right )}{4 \left (x +1\right )}+3 \ln \left (x +1\right )\right )-\frac {12 x}{x +1}+12 \ln \left (x +1\right )\) | \(74\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.44, size = 35, normalized size = 1.59 \begin {gather*} -2 \, {\left (x^{2} {\left (e + 2\right )} - 2 \, x {\left (2 \, e + 1\right )} - \frac {2 \, {\left (2 \, e + 1\right )}}{x + 1}\right )} e^{\left (-1\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 0.55, size = 48, normalized size = 2.18 \begin {gather*} \frac {8\,\mathrm {e}+4}{\mathrm {e}+x\,\mathrm {e}}-x\,\left (12\,{\mathrm {e}}^{-1}-2\,{\mathrm {e}}^{-1}\,\left (4\,\mathrm {e}+8\right )\right )-\frac {x^2\,{\mathrm {e}}^{-1}\,\left (4\,\mathrm {e}+8\right )}{2} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.17, size = 37, normalized size = 1.68 \begin {gather*} - x^{2} \left (\frac {4}{e} + 2\right ) - x \left (-8 - \frac {4}{e}\right ) - \frac {- 8 e - 4}{e x + e} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________